2011
DOI: 10.2522/ptj.20110033
|View full text |Cite
|
Sign up to set email alerts
|

More Than Meets the Eye: Clinical Reflection and Evidence-Based Practice in an Unusual Case of Adolescent Chronic Ankle Sprain

Abstract: Patient symptoms were inconsistent with the medical diagnosis, and the clinical outcome of the original plan of care was unsuccessful. Reflection inspired a more-detailed history and systems review, which led to greater understanding and more-effective care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These indings are consistent with those of authors such as Baumbach et al [5] and Cosby et al [6], concerning the predisposition of injured ankles to recurrent sprains and the possibility of chronic pain or instability after a sprain. Inadequate rehabilitation and previous history of ankle sprain are considered as risk factors for future injuries by Dubin et al [9], Mohamed et al [12], Klykken et al [13], and Lionberger et al [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These indings are consistent with those of authors such as Baumbach et al [5] and Cosby et al [6], concerning the predisposition of injured ankles to recurrent sprains and the possibility of chronic pain or instability after a sprain. Inadequate rehabilitation and previous history of ankle sprain are considered as risk factors for future injuries by Dubin et al [9], Mohamed et al [12], Klykken et al [13], and Lionberger et al [14].…”
Section: Discussionmentioning
confidence: 99%
“…Dubin et al [10] showed that 70% of the basketball players had previous ankle sprain and 80% of them had recurrent sprains. Chronic ankle disorders for instance chronic pain, muscular weaknesses and instability were common for those cases with a previous ankle sprain [11][12][13].…”
Section: Introductionmentioning
confidence: 99%